SERVQUAL IN HIGHER EDUCATION INSTITUTIONS - MANUNGGAL, BAGUS; AFRIADI, BAMBANG (IJBLE Scientific Publications Community Inc., 2023)
Many researchers use SERVQUAL to measure service quality in higher education institutions (HEI). They believe that students are customers and that higher education institution should exceed their expectations. This article uses a literature review to investigate the causes and effects of that paradigm shift. The findings show many negative impacts on treating students as customers such as degrading students-HEI relationship, diverting the orientation of teaching and learning, and contrasting with academic performance. This article suggests that SERVQUAL should not be used to measure the quality of service in higher education institutions.